Optical antenna effect on SiNWs/CuS photodiodes - Yenchalwar, Sandeep G.; Rondiya, Sachin R.; Shinde, Pravin N.; Jadkar, Sandesh R.; Shelke, M. V. (Physica Status Solidi A-Applications and Materials Science, 2017)
One-dimensional architectures between silicon nanowires (SiNWs) and CuS were fabricated by radio-frequency (RF) magnetron sputtering and analyzed for solid-state photodetector application. Inspired by the subwavelength optical concentration by the surface plasmons on metal nanostructures at the nanoscale, we investigated the effect of gold nanorods (AuNRs) on the optical absorption and photodetection properties of the heterojunction photodiode. AuNRs acting as an optical trapping antenna enhances the light absorption, consequently boosting the photocurrent from the device. A maximum photoresponsivity of 0.36 mA W-1 was achieved under 665 nm excitation wavelength independent of the bias, a value similar to 13 times higher than for the heterojunction photodiode without AuNRs. Such plasmonic sensitization can be useful for improving the sensitivity of visible as well as IR photodetectors. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim